Characterization of the Biology Teachers Who Participated in the VII Costa Rican Olympiad of Biological Sciences: A Glance of Their Competitor's Students - Herrera, Federico (2017)
This study aims to understand the strengths and areas of improvement on the teaching and learning process of biological sciences within the classroom; therefore, knowing the perception of students is fundamental. It is generated a baseline that reflects the current situation of the teaching-learning process in order to identify the educational actions that could be further enhanced, and those that need improvement from the teaching perspective. A characterization of the biology teachers who participated in VII Costa Rican Biology Olympiad, 2013, is presented from their students’ perspectives. The results obtained, through the implementation of a survey, were positive since 83% of teachers scored a high qualification in their teaching performance.